PREDICTOR OF ANEMIA AMONG PEOPLE LIVING WITH HIV TAKING TENOFOVIR+LAMIVUDINE+EFAVIRENZ THERAPY IN JAYAPURA, PAPUA - Setyo Adiningsih; Tri Nury Kridaningsih; Mirna Widiyanti; Tri Wahyuni (Universitas Airlangga, 2023)
Background: The most common hematological abnormality among people infected with Human Immunodeficiency Virus (HIV) is anemia. This is also related to high mortality risk among patients receiving Antiretroviral Therapy (ART). Purpose: This study aimed to identify predictorsf anemia among HIV patients taking ART using a regimen of the single-tablet drug contain tenofovir, lamivudine, and efavirenz in Jayapura, Papua. Methods: This was a cross-sectional study conducted at Jayapura regional hospital from June to September 2017. A total of 80 HIV patients were eligible for analysis. Data collection was conducted through an interview, medical record, measurement, and laboratory assay. The significance of differences among categorical variables was analyzed using Fisher's exact test. The variables with p < 0.25 were then analyzed using binary logistic regression to determine predictors associated with anemia. A threshold of p < 0.05 indicates statistical significance. Results: This study showed that Body Mass Index (BMI) <18.50 (p = 0.01; OR = 5.63; 95% CI = 1.43 < OR < 22.19), length onRT ≤12 months (p = 0.00; OR = 4.90; 95% CI = 1.65 < OR < 14.53), and Cluster of Differentiation 4 (CD4+) percentage out of normal (p = 0.02; OR = 0.19; 95% CI = 0.05 < OR <0.77) had a significant association with anemia. Conclusion: BMI, length on ART, and CD4+ percentage were predictors of anemia among HIV patients taking antiretroviral therapy contain tenofovir, lamivudine, efavirenz regimen in Jayapura.